Gfi1aa/Lsd1 Facilitates Hemangioblast Differentiation Into Primitive Erythrocytes by Targeting etv2 and sox7 in Zebrafish - Wu, Mei; Chen, Qi; Li, Jing; Xu, Yue; Lian, Junwei; Liu, Yongxiang; Meng, Ping; Zhang, Yiyue (Frontiers in Cell and Developmental Biology, 2022)
The first wave of hematopoiesis is the primitive hematopoiesis, which produces embryonic erythroid and myeloid cells. Primitive erythrocytes are thought to be generated from bipotent hemangioblasts, but the molecular basis remains unclear. Transcriptional repressors Gfi1aa and Gfi1b have been shown to cooperatively promote primitive erythrocytes differentiation from hemangioblasts in zebrafish. However, the mechanism of these repressors during the primitive wave is largely unknown. Herein, by functional analysis of zebrafish gfi1aasmu10, gfi1bsmu11, gfi1absmu12 single, double, and triple mutants, we found that Gfi1aa not only plays a predominant role in primitive erythropoiesis but also synergizes with Gfi1ab. To screen Gfi1aa downstream targets, we performed RNA-seq and ChIP-seq analysis and found two endothelial transcription factors, etv2 and sox7, to be repressed by Gfi1aa. Genetic analysis demonstrated Gfi1aa to promote hemangioblast differentiation into primitive erythrocytes by inhibiting both etv2 and sox7 in an Lsd1-dependent manner. Moreover, the H3K4me1 level of etv2 and sox7 were increased in gfi1aa mutant. Taken together, these results suggest that Gfi1aa/Lsd1-dependent etv2/sox7 downregulation is critical for hemangioblast differentiation during primitive hematopoiesis by inhibition of endothelialization. The different and redundant roles for Gfi1(s), as well as their genetic and epigenetic regulation during primitive hematopoiesis, help us to better know the molecular basis of the primitive hematopoiesis and sheds light on the understanding the Gfi1(s) related pathogenesis.